Kekuatan Pembuktian Sertipikat Hak Atas Tanah (Konvensional dan Elektronik) - Indira Retno Aryatie; Oemar Moechthar; Angela Melani Widjaja (Perspektif Hukum, 2022)
Land is one of the important elements for social lives. Because really that important, the land which was the one of elements of the agrarian in the life of the Indonesian constitutionality has been regulated in Law Number 5 of 1960. This arrangement is intended to ensure a certainty of legal, in which the land was necessary a land registration in order to provide such certainty and legal protection to the rights holders, their rights which later on the outcome of those with registration certificate as a strong evidence. However due to the development of technology that so rapidly now this, then in terms of registering land even until issue certificates have can be done online/electronic. So that with the latest regulation regarding electronic acticity creates a new problem in terms of proof power between conventional certificates and electronic certificates.